Akal budi dalam sempama jaku Iban (peribahasa) berimejkan mamalia berdasarkan perspektif semantik inkuisitif - Mindew Douglas, Rynna Sha’erra; Subet, Mary Fatimah; Daud, Muhammad Zaid (UUM Press, 2024)
Proverbs have been used by the Iban community to convey values (positive and negative), teachings (advice and guidance), local wisdom, and life experiences. The Iban community also uses symbolic images around them to highlight the relationship between human attitudes or life situations. For example, symbolic images of animals (mammals). Therefore, this study aims to analyze Iban proverbs that use symbolic images of animals (mammals) guided by an inquisitive semantic approach (Nor Hashimah Jalaluddin, 2014). The research data was obtained from Bup Sempama Iban written by Casper Kayong Umping (2011). The results of the study found that, the creation of proverbs involving symbolic images (mammals) in the Iban community is divided into two, namely: (1) ocean life, such as ‘ikan iyu’ and (2) land life, such as ‘mayau’, ‘tupai’, ‘ukui’, ‘jugam’, ‘kera’, ‘kijang’, and ‘empeliau’. In summary, the involvement of symbolic images (mammals) in proverbs can reflect the Iban community’s view of nature and animals as a source of inspiration.